Preclinical evaluation of 99mTc labeled gefitinib as a potential scintigraphic probe for the detection of tumors expressing epidermal growth factor receptors. (May 2015) - Kumar, Pardeep; Singh, Baljinder; Ghai, Anchal; Chuttani, Krishna; Dhawan, Devinder; Mittal, Bhagwant R.; Mishra, Anil K.
Abstract: In the present study, we successfully radiolabeled gefitinib with 99m Tc by direct labeling method. The radio-ligand had radiolabeling efficiency of >95.0% and in vitro stability of >80.0% at 24 h. The radiotracer cleared from blood bi- exponentially. Animal organ biodistribution data indicated hepato- renal excretion of the radiotracer. Scintigraphy carried out in tumor bearing mice (induced by EGFR expressing EAT cell lines) demonstrated that the radiotracer accumulated in the tumor site with T/NT ratio of 3.3±0.2 at 1 h. Highlights: Gefitinib – an epidermal growth factor receptor inhibitor was successfully radiolabeled with 99m Tc and the resultant radiolabel 99m Tc-gefitinib had high radiolabeling efficiency and in vitro stability. The radiotracer cleared from blood bi-exponentially. Animal organ biodistribution data demonstrated hepato-renal excretion of the radiotracer. Gamma camera imaging in tumor bearing mice demonstrated that the radiotracer accumulated in the tumor site with high target to non target ratio. The diagnostic efficacy of 99m Tc- gefitinib needs clinical validation in tumors expressing high EGFR density.